Bibliometrics unleashed: navigating the landscape of classroom assessment - Wan Mat, Wan Fazwani; Lian, Lim Hooi (Intelektual Pustaka Media Utama, 2025)
This bibliometric article examines the current state of publication in the field of classroom assessment, exploring the productivity and influence of countries, institutions, and authors. A search query of on the Scopus database using the term “classroom assessment” or “classroom-based assessment” or “assessment for learning” was performed retrieving 824 scholarly articles from 1985 to 2023. VOSviewer software was used to create maps based on network data of scientific publications displaying relationships among researchers, countries, and scientific journals. By analyzing citation patterns and keywords, it identifies popular themes among scholars and highlights areas requiring further research under keywords such as